Report on National Workshop on Heat Treatment of Steels - Chaudhuri, Bimal (Indian Science Cruiser, 2012)
Indian Institute of Metals Kolkata Chapter conducted a two day National Workshop on Heat Treatment of Steels on 10th and 11th February, 2012 at Birla Industrial & Technological Museum Kolkata. The objective of the programme was to provide an insight into the developments that are taking place in heat treatment industry and to enhance the knowledge base of engineers and technologists. The workshop had lecture and laboratory components with latter consisting of demonstration of microstructures and interpreting the microstructures before and after the heat treatment operation of various grades of steels.